Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Heterogeneous diversification dynamics reshaped early Paleozoic marine evolutionary history - Minghao Du; Yong Wang; Jingqiang Tan; Wenhui Wang; Ruining Hu; Thomas J. Algeo; Richard A. Boyle; David A.T. Harper; Thomas Servais (Earth-Science Reviews, 2026)

The impact of climate change on the flux and fate of metals in freshwater systems: Implications for metal exposure across different scales - Farhan R. Khan; Nicolas R. Bury; Christopher A. Cooper; David Boyle; Elizabeth Middleton; Simon D. Herzog (Environmental Research, 2025)

Portable luminescence for rapidly identifying tsunami dynamics and responses in saltmarshes - Rachel Smedley; Natascia Pannozzo; John Boyle; David Clarke; Javier Lario; Andrew Plater (Science of The Total Environment, 2025)

A regional coastal Douglas-fir index of site quality for young stands in western Washington, USA - Grady Boyle; David R. Carter; Robert Slesak; Valerie Thomas; Brian Strahm (Forest Ecology and Management, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Animal-borne sensors reveal high human impact on soundscapes near a critical sea turtle nesting beach - Francesco Garzon; Pierre Didier Agamboue; Jack A. Boyle; Philip D. Doherty; Angela Formia; Brendan J. Godley; Lucy A. Hawkes; David A. Mann; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Guy-Phillipe Sounguet; et al. (Biological Conservation, 2024)

Differential correlations of changes in in vivo neuroimaging markers of hippocampal volume and arteriolosclerosis with declining financial and health literacy in old age - Lei Yu; Tianhao Wang; Alifiya Kapasi; Melissa Lamar; Gary Mottola; Konstantinos Arfanakis; David A. Bennett; Patricia A. Boyle (Brain Imaging and Behavior, 2024)

Associations between structural neuroimaging markers of Alzheimer’s risk and scam susceptibility - Melissa Lamar; Konstantinos Arfanakis; Alifiya Kapasi; S. Duke Han; David A. Bennett; Lei Yu; Patricia A. Boyle (Brain Imaging and Behavior, 2024)

A comparison of dermal toxicity models; assessing suitability for safe(r)-by-design decision-making and for screening nanomaterial hazards - Polly McLean; Jessica Marshall; Amaia García-Bilbao; David Beal; Alberto Katsumiti; Marie Carrière; Matthew S.P. Boyles (Toxicology in Vitro, 2024)

Comparison of toxicity of silver nanomaterials and silver nitrate on developing zebrafish embryos: Bioavailability, osmoregulatory and oxidative stress - Susana P.P. Pereira; David Boyle; António J.A. Nogueira; Richard D. Handy (Chemosphere, 2023)

Modeling historic neighborhood deprivation and non-Hodgkin lymphoma risk - Joseph Boyle; Mary H. Ward; James R. Cerhan; Nathaniel Rothman; David C. Wheeler (Environmental Research, 2023)

Modeling historic environmental pollutant exposures and non-Hodgkin lymphoma risk - Joseph Boyle; Mary H. Ward; James R. Cerhan; Nathaniel Rothman; David C. Wheeler (Environmental Research, 2023)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A review of the heterogeneous landscape of biodiversity databases: Opportunities and challenges for a synthesized biodiversity knowledge base - Xiao Feng; Brian J. Enquist; Daniel S. Park; Brad Boyle; David D. Breshears; Rachael V. Gallagher; Aaron Lien; Erica A. Newman; Joseph R. Burger; Brian S. Maitner; Cory Merow; Yaoqi Li; et al. (Global Ecology and Biogeography, 2022)
Aim Addressing global environmental challenges requires access to biodiversity data across wide spatial, temporal and taxonomic scales. Availability of such data has increased exponentially recently with the proliferation of biodiversity databases. However, heterogeneous coverage, protocols, and standards have hampered integration among these databases. To stimulate the next stage of data integration, here we present a synthesis of major databases, and investigate (a) how the coverage of databases varies across taxonomy, space, and record type; (b) what degree of integration is present among databases; (c) how integration of databases can increase biodiversity knowledge; and (d) the barriers to database integration. Location Global. Time period Contemporary. Major taxa studied Plants and vertebrates. Methods We reviewed 12 established biodiversity databases that mainly focus on geographic distributions and functional traits at global scale. We synthesized information from these databases to assess the status of their integration and major knowledge gaps and barriers to full integration. We estimated how improved integration can increase the data coverage for terrestrial plants and vertebrates. Results Every database reviewed had a unique focus of data coverage. Exchanges of biodiversity information were common among databases, although not always clearly documented. Functional trait databases were more isolated than those pertaining to species distributions. Variation and potential incompatibility of taxonomic systems used by different databases posed a major barrier to data integration. We found that integration of distribution databases could lead to increased taxonomic coverage that corresponds to 23 years’ advancement in data accumulation, and improvement in taxonomic coverage could be as high as 22.4% for trait databases. Main conclusions Rapid increases in biodiversity knowledge can be achieved through the integration of databases, providing the data necessary to address critical environmental challenges. Full integration across databases will require tackling the major impediments to data integration: taxonomic incompatibility, lags in data exchange, barriers to effective data synchronization, and isolation of individual initiatives.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Characterisation of an Australian fowlpox virus carrying a near-full-length provirus of reticuloendotheliosis virus - Subir Sarker; Ajani Athukorala; Timothy R. Bowden; David B. Boyle (Archives of Virology, 2021)

Limited evidence for negative effects of highway widening on North American large mammals - Sean P. Boyle; Jacqueline D. Litzgus; David Lesbarrères (European Journal of Wildlife Research, 2020)

White matter correlates of scam susceptibility in community-dwelling older adults - Melissa Lamar; Konstantinos Arfanakis; Lei Yu; Shengwei Zhang; S. Duke Han; Debra A. Fleischman; David A. Bennett; Patricia A. Boyle (Brain Imaging and Behavior, 2020)

Feasibility of the Bag-Mediated Filtration System for Environmental Surveillance of Poliovirus in Kenya - Nicolette A. Zhou; Christine S. Fagnant-Sperati; Evans Komen; Benlick Mwangi; Johnstone Mukubi; James Nyangao; Joanne Hassan; Agnes Chepkurui; Caroline Maina; Walda B. van Zyl; Peter N. Matsapola; Marianne Wolfaardt; et al. (Food and Environmental Virology, 2020)
The bag-mediated filtration system (BMFS) was developed to facilitate poliovirus (PV) environmental surveillance, a supplement to acute flaccid paralysis surveillance in PV eradication efforts. From April to September 2015, environmental samples were collected from four sites in Nairobi, Kenya, and processed using two collection/concentration methodologies: BMFS (> 3 L filtered) and grab sample (1 L collected; 0.5 L concentrated) with two-phase separation. BMFS and two-phase samples were analyzed for PV by the standard World Health Organization poliovirus isolation algorithm followed by intratypic differentiation. BMFS samples were also analyzed by a cell culture independent real-time reverse transcription polymerase chain reaction (rRT-PCR) and an alternative cell culture method (integrated cell culture-rRT-PCR with PLC/PRF/5, L20B, and BGM cell lines). Sabin polioviruses were detected in a majority of samples using BMFS (37/42) and two-phase separation (32/42). There was statistically more frequent detection of Sabin-like PV type 3 in samples concentrated with BMFS (22/42) than by two-phase separation (14/42, p = 0.035), possibly due to greater effective volume assayed (870 mL vs. 150 mL). Despite this effective volume assayed, there was no statistical difference in Sabin-like PV type 1 and Sabin-like PV type 2 detection between these methods (9/42 vs. 8/42, p = 0.80 and 27/42 vs. 32/42, p = 0.18, respectively). This study demonstrated that BMFS can be used for PV environmental surveillance and established a feasible study design for future research.

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Toreforant, an orally active histamine H4-receptor antagonist, in patients with active rheumatoid arthritis despite methotrexate: mechanism of action results from a phase 2, multicenter, randomized, double-blind, placebo-controlled synovial biopsy study - David L. Boyle; Samuel E. DePrimo; Cesar Calderon; Dion Chen; Paul J. Dunford; William Barchuk; Gary S. Firestein; Robin L. Thurmond (Inflammation Research, 2019)

Evaluation of Secondary Concentration Methods for Poliovirus Detection in Wastewater - Jill C. Falman; Christine S. Fagnant-Sperati; Alexandra L. Kossik; David S. Boyle; John Scott Meschke (Food and Environmental Virology, 2019)

White matter correlates of temporal discounting in older adults - S. Duke Han; Konstantinos Arfanakis; Debra A. Fleischman; Lei Yu; David A. Bennett; Patricia A. Boyle (Brain Structure and Function, 2018)

Improvement of the Bag-Mediated Filtration System for Sampling Wastewater and Wastewater-Impacted Waters - Christine Susan Fagnant; Liliana Margarita Sánchez-Gonzalez; Nicolette A. Zhou; Jill Christin Falman; Michael Eisenstein; Dylan Guelig; Byron Ockerman; Yifei Guan; Alexandra Lynn Kossik; Yarrow S. Linden; Nicola Koren Beck; Robyn Wilmouth; et al. (Food and Environmental Virology, 2018)

Use of Preservative Agents and Antibiotics for Increased Poliovirus Survival on Positively Charged Filters - Christine Susan Fagnant; Alexandra Lynn Kossik; Nicolette Angela Zhou; Liliana Sánchez-Gonzalez; Jill Christin Falman; Erika Karen Keim; Yarrow Linden; Alana Scheibe; Kilala Sayisha Barnes; Nicola Koren Beck; David S. Boyle; John Scott Meschke (Food and Environmental Virology, 2017)

Comparison of road surveys and circuit theory to predict hotspot locations for implementing road-effect mitigation - S. P. Boyle; J. D. Litzgus; David Lesbarrères (Biodiversity and Conservation, 2017)

Development of an elution device for ViroCap virus filters - Christine Susan Fagnant; Matthew Toles; Nicolette Angela Zhou; Jacob Powell; John Adolphsen; Yifei Guan; Byron Ockerman; Jeffry Hiroshi Shirai; David S. Boyle; Igor Novosselov; John Scott Meschke (Environmental Monitoring and Assessment, 2017)

Grey matter correlates of susceptibility to scams in community-dwelling older adults - S. Duke Han; Patricia A. Boyle; Lei Yu; Konstantinos Arfanakis; Bryan D. James; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Oxygen Mass Transport in Stented Coronary Arteries - Eoin A. Murphy; Adrian S. Dunne; David M. Martin; Fergal J. Boyle (Annals of Biomedical Engineering, 2016)

Sequential Structural and Fluid Dynamics Analysis of Balloon-Expandable Coronary Stents: A Multivariable Statistical Analysis - David Martin; Fergal Boyle (Cardiovascular Engineering and Technology, 2015)

Gray-matter macrostructure in cognitively healthy older persons: associations with age and cognition - Debra A. Fleischman; Sue Leurgans; Konstantinos Arfanakis; Zoe Arvanitakis; Lisa L. Barnes; Patricia A. Boyle; S. Duke Han; David A. Bennett (Brain Structure and Function, 2014)

Characterization of 10 polymorphic microsatellite loci in Munidopsis lauensis, a squat-lobster from the southwestern Pacific - Emily A. Boyle; Andrew David Thaler; Alixandra Jacobson; Sophie Plouviez; Cindy Lee Van Dover (Conservation Genetics Resources, 2013)

A birth cohort analysis of the incidence of ascending and descending colon cancer in the United States, 1973–2008 - Cairong Zhu; Bryan A. Bassig; David Zaridze; Peter Boyle; Min Dai; Qian Li; Tongzhang Zheng (Cancer Causes & Control, 2013)

Effects of insect activity, soil, and cuticular factors on virulence of Beauveria bassiana toward Blissus leucopterus hirtus - David Boyle; G. Christopher Cutler (Journal of Pest Science, 2012)

Persistent and recrudescent infection in cattle following natural infection with Middle Point orbivirus - Christopher Cowled; Lorna Melville; Richard Weir; Susan Walsh; Aneta Gubala; Steven Davis; David Boyle (Archives of Virology, 2012)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Genetic variation in N-acetyltransferases 1 and 2, cigarette smoking, and risk of non-Hodgkin lymphoma - Briseis A. Kilfoy; Tongzhang Zheng; Qing Lan; Xuesong Han; Theodore Holford; David W. Hein; Qin Qin; Brian Leaderer; Lindsay M. Morton; Meredith Yeager; Peter Boyle; Ping Zhao; et al. (Cancer Causes & Control, 2010)

Community composition of ammonia‐oxidizing bacteria and archaea in soils under stands of red alder and Douglas fir in Oregon - Stephanie A. Boyle‐Yarwood; Peter J. Bottomley; David D. Myrold (Environmental Microbiology, 2008)
Summary This study determined nitrification activity and nitrifier community composition in soils under stands of red alder ( Alnus rubra ) and Douglas fir ( Pseudotsuga menziesii ) at two sites in Oregon. The H.J. Andrews Experimental Forest, located in the Cascade Mountains of Oregon, has low net N mineralization and gross nitrification rates. Cascade Head Experimental Forest, in the Coast Range, has higher net N mineralization and nitrification rates and soil pH is lower. Communities of putative bacterial [ammonia‐oxidizing bacteria (AOB)] and archaeal [ammonia‐oxidizing archaea (AOA)] ammonia oxidizers were examined by targeting the gene amoA , which codes for subunit A of ammonia monooxygenase. Nitrification potential was significantly higher in red alder compared with Douglas‐fir soil and greater at Cascade Head than H.J. Andrews. Ammonia‐oxidizing bacteria amoA genes were amplified from all soils, but AOA amoA genes could only be amplified at Cascade Head. Gene copy numbers of AOB and AOA amoA were similar at Cascade Head regardless of tree type (2.3–6.0 × 10 6 amoA gene copies g −1 of soil). DNA sequences of amoA revealed that AOB were members of Nitrosospira clusters 1, 2 and 4. Ammonia‐oxidizing bacteria community composition, determined by terminal restriction fragment length polymorphism (T‐RFLP) profiles, varied among sites and between tree types. Many of the AOA amoA sequences clustered with environmental clones previously obtained from soil; however, several sequences were more similar to clones previously recovered from marine and estuarine sediments. As with AOB, the AOA community composition differed between red alder and Douglas‐fir soils.

Corrigendum: Population pharmacokinetics of S(-)-carvedilol in healthy volunteers after administration of the immediate-release (IR) and the new controlled-release (CR) dosage forms of the racemate - Ahmed A. Othman; David M. Tenero; Duane A. Boyle; Natalie D. Eddington; Michael J. Fossler (The AAPS Journal, 2007)

Population pharmacokinetics of S(−)-carvedilol in healthy volunteers after administration of the immediate-release (IR) and the new controlled-release (CR) dosage forms of the racemate - Ahmed A. Othman; David M. Tenero; Duane A. Boyle; Natalie D. Eddington; Michael J. Fossler (The AAPS Journal, 2007)

Genetic Typing of Classical Swine Fever Viruses from Lao PDR by Analysis of the 5′ Non-Coding Region - Stuart D. Blacksell; Syseng Khounsy; David B. Boyle; Laurence J. Gleeson; Harvey A. Westbury; John S. Mackenzie (Virus Genes, 2005)

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)

Phylogenetic Analysis of the DNA Polymerase Gene of a Novel Alphaherpesvirus Isolated from an Indian Gyps Vulture - Maria Cardoso; Alex Hyatt; Paul Selleck; Sue Lowther; Vibhu Prakash; Deborah Pain; Andrew A. Cunningham; David Boyle (Virus Genes, 2005)

Nucleic acid vaccines - Brent S. McKenzie; Alexandra J. Corbett; Jamie L. Brady; Christopher M. Dyer; Richard A. Strugnell; Stephen J. Kent; David R. Kramer; Jefferey S. Boyle; Andrew M. Lew (Immunologic Research, 2001)